Synergistic enhancement of recycled aggregate concrete using hybrid natural-synthetic fiber reinforcement and silica fume - Danish Akbar; Faisal Shabbir; Ali Raza; Nabil Ben Kahla (Results in Engineering)
This study explores the synergistic influence of hybrid fiber reinforcement (combining natural coconut fibers and synthetic carbon fibers) and varying levels of silica fume (SF) on the mechanical and durability properties of recycled aggregate concrete (RAC). A constant total fiber content of 1.5 % was maintained across all mixtures, while SF was incorporated at 5 %, 10 %, and 15 % as a partial cement replacement. Mechanical performance was evaluated through compressive, flexural, and splitting tensile strength tests, while durability was assessed via water absorption, mercury intrusion porosimetry (MIP), and acid resistance testing. Microstructural and mineralogical characterizations were performed using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FTIR). One-way analysis of variance (ANOVA) test was also performed to examine the statistical significance of the results. The results demonstrated significant enhancements in both mechanical and durability performance, particularly in carbon fiber-dominant mixes. Compared to the control, compressive, flexural, and splitting tensile strengths increased by up to 12.89 %, 11.42 %, and 65.17 %, respectively. Durability improvements included a reduction in water absorption by up to 45.06 % and a 63.83 % decrease in acid-induced mass loss after 28 days. SEM images revealed denser interfacial transition zones (ITZ) and a more compact microstructure, attributed to the pozzolanic activity of silica fume and the effective crack-bridging behavior of the fibers. XRD and FTIR analyses confirmed increased formation of calcium silicate hydrate (C–S–H) and a marked reduction in calcium hydroxide (Ca(OH)₂), indicating improved long-term durability. The findings demonstrate that the optimal combination of carbon-coconut hybrid fibers and 15 % silica fume significantly enhances mechanical strength, acid resistance, and matrix densification. These results highlight a sustainable pathway for improving the durability and structural integrity of recycled aggregate concrete.